High Dose of Acute Normobaric Hypoxia Does Not Adversely Affect Sprint Interval Training, Cognitive Performance and Heart Rate Variability in Males and Females - Karayigit, Raci; Ramirez-Campillo, Rodrigo; Yasli, Burak Caglar; Gabrys, Tomasz; Benesova, Daniela; Esen, Ozcan (Biology, 2022)
Although preliminary studies suggested sex-related differences in physiological responses to hypoxia, the effects of sex on sprint interval training (SIT) performance in different degrees of hypoxia are largely lacking. The aim of this study was to examine the acute effect of different doses of normobaric hypoxia on SIT performance as well as heart rate variability (HRV) and cognitive performance (CP) in amateur-trained team sport players by comparing potential sex differences. In a randomized, double-blind, crossover design, 26 (13 females) amateur team-sport (football, basketball, handball, rugby) players completed acute SIT (6 × 15 s all-out sprints, separated with 2 min active recovery, against a load equivalent to 9% of body weight) on a cycle ergometer, in one of four conditions: (I) normoxia without a mask (FiO2: 20.9%) (CON); (II) normoxia with a mask (FiO2: 20.9%) (NOR); (III) moderate hypoxia (FiO2: 15.4%) with mask (MHYP); and (IV) high hypoxia (FiO2: 13.4%) with mask (HHYP). Peak (PPO) and mean power output (MPO), HRV, heart rate (HR), CP, capillary lactate (BLa), and ratings of perceived exertion (RPE) pre- and post-SIT were compared between CON, NOR, MHYP and HHYP. There were no significant differences found between trials for PPO (p = 0.55), MPO (p = 0.44), RPE (p = 0.39), HR (p = 0.49), HRV (p > 0.05) and CP (response accuracy: p = 0.92; reaction time: p = 0.24). The changes in MP, PP, RPE, HR, CP and HRV were similar between men and women (all p > 0.05). While BLa was similar (p = 0.10) between MHYP and HHYP trials, it was greater compared to CON (p = 0.01) and NOR (p = 0.01), without a sex-effect. In conclusion, compared to normoxia, hypoxia, and wearing a mask, have no effect on SIT acute responses (other than lactate), including PP, MP, RPE, CP, HR, and cardiac autonomic modulation either in men or women.
Keywords: human physical conditioning; altitude; sex; high-intensity interval training